ARTIFICIAL INTELLIGENCE AND THE TRANSFORMATION OF THE ACCOUNTING PROFESSION: A SYSTEMATIC LITERATURE REVIEW OF OPPORTUNITIES, CHALLENGES, AND FUTURE IMPLICATIONS - Iwan Sunu Purwoko (Universitas Tulungagung, 2026)
Artificial Intelligence (AI) has significantly transformed accounting practices and the accounting profession through technologies such as Machine Learning (ML), Robotic Process Automation (RPA), Natural Language Processing (NLP), Big Data Analytics, and blockchain. While AI improves efficiency, automation, financial reporting, auditing, and decision-making, it also introduces challenges related to ethical governance, cybersecurity, algorithmic bias, technological dependency, and workforce transformation. This study aims to examine the impact of AI on accounting practices and the accounting profession using a Systematic Literature Review (SLR) approach. Following the PRISMA framework, 31 peer-reviewed studies published between 2022 and 2026 were selected and analyzed using thematic analysis. The findings indicate that AI enhances operational efficiency, audit quality, fraud detection, real-time financial reporting, and strategic decision-making. Furthermore, AI reshapes accountants' roles from routine administrative functions toward more analytical, strategic, and advisory responsibilities, increasing the need for digital competencies, AI literacy, and ethical awareness. This study contributes to the accounting literature by providing an integrated synthesis of the opportunities, challenges, and future implications of AI adoption. It also highlights the importance of continuous professional development, technology-oriented accounting education, and ethical governance to support sustainable AI implementation in the accounting profession.